ch03-p036 - 36 We apply Eq 3-30 and Eq 3-23(a a b =(ax by a...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
We therefore obtain 22 (3.0)(2.0) (5.0)(4.0) ˆ 5.8. (2.0) (4.0) b aa b + =⋅= = + G 36. We apply Eq. 3-30 and Eq. 3-23. (a) ˆ = ( ) k xy yx ab a b ab ×− G G since all other terms vanish, due to the fact that neither G a nor G b have any z components. Consequently, we obtain ˆˆ [(3.0)(4.0) (5.0)(2.0)]k 2.0k −= . (b) = x y ab ab ab ⋅+ G yields (3.0)(2.0) + (5.0)(4.0) = 26. (c) (3.0 2.0) i (5.0 4.0) j ab += +
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 05/17/2011 for the course PHY 2049 taught by Professor Any during the Spring '08 term at University of Florida.

Ask a homework question - tutors are online